2018
DOI: 10.1159/000492784
|View full text |Cite
|
Sign up to set email alerts
|

Depression Symptoms Predict Worse Clinical Response to Etanercept Treatment in Psoriasis Patients

Abstract: Background/Aims: This study aimed to investigate the predicting values of depression and anxiety symptoms for clinical response to etanercept treatment in psoriasis patients. Methods: A total of 85 psoriasis patients who received 6 months of etanercept treatment were consecutively enrolled in this prospective cohort study. The Psoriasis Area and Severity Index (PASI) score was evaluated at month 0 (M0), M1, M3, and M6, and the corresponding PASI 75/90 response at each visit was assessed. Also, anxiety and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…This is in line with data from the published work indicating that depending on the screening methodology, depressive symptoms are present in 9–55% of psoriatic patients 55 . Depressive symptoms at baseline may predict a worse clinical response to antipsoriatic treatment 56 . Furthermore, therapeutic options for psoriatic patients with comorbid depression are more limited compared with patients without depression.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in line with data from the published work indicating that depending on the screening methodology, depressive symptoms are present in 9–55% of psoriatic patients 55 . Depressive symptoms at baseline may predict a worse clinical response to antipsoriatic treatment 56 . Furthermore, therapeutic options for psoriatic patients with comorbid depression are more limited compared with patients without depression.…”
Section: Discussionsupporting
confidence: 88%
“…55 Depressive symptoms at baseline may predict a worse clinical response to antipsoriatic treatment. 56 Furthermore, therapeutic options for psoriatic patients with comorbid depression are more limited compared with patients without depression. In most of the cases, depression and suicidal ideation behavior represent an exclusion criterion for participation in clinical trials with new compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Such psychiatric comorbidities can aggravate the condition, delay recovery, impair treatment or even accelerate the recurrence of psoriasis. Also, they contribute to increased consumption of alcohol and tobacco, with potential worsening to the disease (Jin et al, 2019; Koo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, carried out by Bronikowska-Kolasa et al 43 in a group of 110 patients, PASI scores ranged from 1 to 27.3 pts, with the mean value of 12.7 ±5.6 pts corresponding to moderate to severe psoriasis. Jin et al 44 followed 85 patients with psoriasis for six months of etanercept treatment, assessing their PASI 75/90 response at each visit. The study demonstrated that depression symptoms at the baseline were associated with worse clinical response to etanercept, as shown by reduced PASI 75/90 response rates.…”
Section: Discussionmentioning
confidence: 99%